The effect of public–private partnership investment, financial development, and renewable energy consumption on the ecological footprint in South Asia and the Pacific region - Wen, Ya; Qu, Chenchen; Gao, Chen; Song, Pingting; Yang, Deyong (Frontiers in Environmental Science, 2022)
The improvement of environmental quality has become a major challenge for all countries. Against the strategic background of environmental protection, this current study investigated the role of public-private partnership investment (PPPI) in energy and transport, financial development and renewable energy on ecological footprint (EF) in South Asia and Pacific region, utilizing the autoregressive distributive lag (ARDL) model spanning the time 1990-2017. The outcomes of the ARDL show that PPPI in energy and transport have significantly positive effect on the EF in the full sample and Pacific region in the long run. Financial development has a positive impact on the EF in South Asia and the Pacific region in the long term. Renewable energy causes significantly and negatively impact on the EF in the full sample in both time periods, and only in the short run in South Asia. As for the panel granger causalities test, the PPPI in energy and transport and renewable energy have negative causal relationship with the EF. The results also reveal that there is a unidirectional negative and positive causality from financial development to the EF in the long term in South Asia and Pacific region respectively. On the basis of the analysis, corresponding recommendations are proposed.